2021
DOI: 10.1161/circresaha.121.319737
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resident Macrophages Prevent Fibrosis and Stimulate Angiogenesis

Abstract: Rationale: The initial hypertrophy response to cardiac pressure overload is considered compensatory, but with sustained stress, it eventually leads to heart failure. Recently, a role for recruited macrophages (mψs) in determining the transition from compensated to decompensated hypertrophy has been established. However, whether cardiac-resident immune cells influence the early phase of hypertrophy development has not been established. Objective: To asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 39 publications
(69 reference statements)
7
113
0
1
Order By: Relevance
“…Studies on cardiac remodeling after tissue injury (e.g. myocardial infarction) revealed that macrophages play a pivotal role in cardiac remodeling as they may have both profibrotic and antifibrotic functions ( Wynn and Barron, 2010 ; Liao et al, 2018 ; Revelo et al, 2021 ; Dobaczewski et al, 2011 ). CD68 + or CD11c + macrophages infiltrate the epicardial adipose tissue of AF patients and are associated with atrial fibrotic remodeling leading to a proarrhythmic substrate for AF ( Abe et al, 2018 ).…”
Section: Cardiac Macrophages Mediate Arrhythmogenesis By Promoting Ca...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on cardiac remodeling after tissue injury (e.g. myocardial infarction) revealed that macrophages play a pivotal role in cardiac remodeling as they may have both profibrotic and antifibrotic functions ( Wynn and Barron, 2010 ; Liao et al, 2018 ; Revelo et al, 2021 ; Dobaczewski et al, 2011 ). CD68 + or CD11c + macrophages infiltrate the epicardial adipose tissue of AF patients and are associated with atrial fibrotic remodeling leading to a proarrhythmic substrate for AF ( Abe et al, 2018 ).…”
Section: Cardiac Macrophages Mediate Arrhythmogenesis By Promoting Ca...mentioning
confidence: 99%
“…Pro-inflammatory macrophages release cytokines and chemokines and have been demonstrated to be involved in electrical ( Monnerat et al, 2016 ; Sun et al, 2016 ; Fei et al, 2019 ; Liu et al, 2019 ; Zhang et al, 2020 ) as well as autonomic remodeling of the heart ( Yin et al, 2016 ; Hu et al, 2019 ; Lyu et al, 2020 ; Zhang et al, 2021 ). Noncanonical reparative (or alternatively-activated) macrophages release anti-inflammatory cytokines, participate in post-inflammatory tissue repair, and contribute to cardiac structural remodeling by promoting cardiac fibrosis ( Wynn and Barron, 2010 ; Dobaczewski et al, 2011 ; Mills, 2012 ; Liao et al, 2018 ; Miyosawa et al, 2020 ; Watson et al, 2020 ; Hiram et al, 2021 ; Revelo et al, 2021 ). Furthermore, it has been shown that cardiac resident macrophages are functionally connected to cardiomyocytes by gap junctions ( Simon-Chica et al, 2022 ), thereby facilitating the physiologic electrical conduction in the atrioventricular (AV) node ( Hulsmans et al, 2017 ) or preserving electrical conduction in the context of disease ( Sugita et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a potential protective role of self-renewing resident-Mφ (CCR 2 − ) has emerged from recent studies [ 137 , 156 , 169 , 172 , 173 ] ( Figure 4 ).…”
Section: Macrophages Subsets and Cardiac Remodelingmentioning
confidence: 99%
“…In addition, VEGF secreted by resident Mφ is a well-known key mediator of angiogenesis, e.g., in response to TAC [ 172 , 173 ] ( Figure 4 ).…”
Section: Macrophages Subsets and Cardiac Remodelingmentioning
confidence: 99%
See 1 more Smart Citation